Effect Of Resource Management On Students’ Satisfaction In ISO 9001: 2008 Certified Universities In Kenya - Kandie, Hilary Kipchirchir; Guyo, Wario; Senaji, Thomas A. (Archives of Business Research, 2018)
In the present competitive business environment, quality of products and/service offered by any organization play an important role in determining the satisfaction of the customer. Customer satisfaction on the other hand contributes to firm performance. Similar to other organizations, universities endeavor to ensure quality of their service is attractive to the customers. To enhance the confidence in the quality of teaching, learning and research, most Universities in Kenya choose to be certified on ISO 9001 quality management standard. The Standard requires the organizations to establish a quality management system (QMS) to ensure provision of quality services and products that satisfy the customers. Since quality of university education has been a subject of concern in Kenya, there is need to understand what action is being taken to address the quality concerns. It is against this background that the study sought to establish the role of resource management based on ISO 9001 standard on the students’ satisfaction in ISO 9001:2008 certified universities in Kenya. A sample of 384 students drawn from all the 24 certified universities participated in the study. Data was collected using questionnaires. Quantitative data analysis methods used to generate frequency distribution, descriptive and inferential statistics. Specifically, ordered probit regression model was used to analyse the data using STATA software whereas chi squire test was used to test the hypotheses related to students’ satisfaction. The findings established that resource management enhanced the students’ satisfaction among the ISO 9001 certified universities in Kenya. The inferential statistics analysis revealed that resource management was positively and significantly related to students’ satisfaction. It is concluded that ISO 9001 certified universities in Kenya had better students’ satisfaction as a result of resource management. Based on the findings it is recommended that the universities should embrace better strategies to enhance the satisfaction of the students through resource management, a better effective leadership management, enhance product realisation and cultivate a culture of improvement management of the Quality Management Systems (QMS).